Aspek Permodalan, Kualitas Aset, Manajemen, Efisiensi, Likuiditas dan Sensitivitas Risiko Pasar dalam Menentukan Kinerja Keuangan Sektor Perbankan di Bursa Efek Indonesia - Tinneke Hermina; Wufron Wufron (Fakultas Ekonomi Universitas Garut, 2018)
This research was conducted to determine the effect of capital aspects, asset quality, management aspects, efficiency, liquidity and risk sensitivity of banks on financial performance. Capital aspects are measured by capital adequacy ratio, asset quality is measured by net performing loans, management aspects are measured by net profit margin, efficiency is measured by net interest margin, liquidity is measured by loan-to-deposit ratio, sensitivity to bank risk is measured by market risk, while performance finance is measured by return on assets. This study uses a sample of banking companies listed on the Indonesia Stock Exchange (IDX) in 2016. The data used is cross section data. The data analysis technique used is multiple regression analysis. The results showed that the capital aspect had a positive and significant effect on financial performance, asset quality had a positive and significant effect on financial performance, management had a positive and significant effect on financial performance, efficiency had a positive and insignificant effect on financial performance, liquidity had a negative and significant effect on financial performance. financial performance and sensitivity to risk have a negative and significant effect on financial performance.